Analysis of Tsunami Economic Loss in Tourism Areas Using High-Resolution Tsunami Run-Up Model - Wiwin Windupranata; Alqinthara Nuraghnia; Muhammad Wahyu Al Ghifari; Sonia Kartini Pasaribu; Wiwin Indira Rakhmanisa; Tiara Vani; Kevin Agriva Ginting; Michael Bintang Aventa; Intan Hayatiningsih; Deni Suwardhi; Irwan Meilano; Iyan Eka Mulia; et al. (GeoHazards)
A tsunami can cause significant economic losses for tourism areas like Batukaras Village, which is located on the southern coast of Java Island. This paper seeks to elaborate on the calculation of economic losses in tourism areas due to damage to buildings, loss of land production, and loss of income, based on high-resolution geospatial data. The data are derived from UAV photogrammetry surveys and high-resolution tsunami run-up models. The tsunami worst-case scenario run-off model provides an inundation area of 43 ha with 185 buildings and 24.4 ha of productive land. The estimated losses from the tsunami disaster amounted to IDR 208.79 billion, consisting of 49.63 billion from building damage, 6.73 billion from productive land, and 152.43 billion from the tourism sector. These results show that the tsunami disaster will severely affect tourism areas, because the tourism sector makes up 73% of the total economic losses. Reductions in the amount of economic loss, in addition to spatial planning near the coastline to reduce the number of impacted buildings and productive land, can be achieved by accelerating the recovery period so that economic activities after the tsunami disaster can be carried out immediately, including in the tourism sector.